Clinical development of an anti-GPC-1 antibody for the treatment of cancer. (4th May 2022) - Ghosh, Saikat; Huda, Pie; Fletcher, Nicholas; Campbell, Douglas; Thurecht, Kristofer J.; Walsh, Bradley
ABSTRACT: Introduction: Glypican-1 (GPC-1) is a heparan sulfate proteoglycan (HSPG) overexpressed in multiple cancers. Multiple studies indicate the prominence of this cancer biomarker with significant diagnostic and therapeutic potential. Recent advances in monoclonal antibody (mAb)-based biopharmaceuticals targeting GPC-1 show promise toward managing GPC-1-positive solid tumors clinically. Areas covered: This review addresses GPC-1 targeting antibodies for cancer therapy, in preclinical and clinical development. Current and emerging development of different anti-GPC-1 antibody formats based on mechanism of action and application are also discussed. Expert opinion: Clinical development of novel anti-GPC-1 antibody-based formats is still in its early days. Using the patented anti-GPC-1 Miltuximab® as a case study, we have made an attempt to illustrate a pathway for preclinical to clinical translation, which could be useful for newer GPC-1 targeting immunotherapy agents.